THE ROLE AND IMPORTANCE OF ANTIOXIDANTS IN SCIENTIFIC RESEARCH - Mukhammadiy Khakimiv (Web of Journals Publishing, 2025)
Antioxidants are compounds that are gaining more and more importance in modern medicine and health sciences. These molecules play a critical role in the protection of cells and tissues by preventing oxidative stress caused by free radicals. Oxidative stress occurs as a result of free radicals such as reactive oxygen species (ROS) and reactive nitrogen species (RNS) interacting with cellular components and damaging DNA, proteins and lipids. This process is closely associated with many pathological conditions, such as cancer, cardiovascular diseases, neurodegenerative disorders (such as Alzheimer's, Parkinson's), and even aging. Antioxidants help to prevent cellular damage by neutralizing these harmful molecules.